Dry Eye Disease in Patients With Schizophrenia: A Case-Control Study - Chen, Qiankun; Wei, Zhengjiang; Wang, Leying; Xu, Xizhan; Wei, Zhenyu; Zheng, Panpan; Cao, Kai; Zhang, Zijun; Chen, Kexin; Liang, Qingfeng (Frontiers in Medicine, 2022)
Objective: To evaluate the clinical features and inflammatory cytokines of dry eye disease (DED) in patients with schizophrenia. Methods: Case-control study. Modified self-rating depression scale (M-SDS) and ocular surface disease index (OSDI) were used to evaluate the symptoms of depression and DED respectively. Lipid layer thickness (LLT), partial blink rate (PBR), meibomian gland loss (MGL), tear brake-up time (TBUT), corneal fluorescein staining, Schirmer I test and eyelid margin abnormalities were also measured. A multiplex ELISA Quantibody array was used to detect the inflammatory cytokines in tears of all participants. Results: Forty schizophrenic patients and 20 control subjects were included. The mean age was 45.0±9.5 years (range, 22-63 years) in schizophrenic patients and 45.4±16.2 years (range, 23-76 years) in controls (P = 0.914). The ratio of males to females was 1.1 in schizophrenic patients and 1.0 in controls (P = 0.914). Ten females (52.6%) with schizophrenia were menopausal or post-menopausal and two (20%) in the control group (P = 0.096). The OSDI [0.0(0.0-4.2) vs. 7.3(2.1-14.6)] and TBUT [4.5(3.0-6.0) vs. 10.0(3.5-11.0)] were significantly lower in patients with schizophrenia than controls (P=0.003; P=0.009, respectively). The rate of MGL [36.5(17.5-47.5) vs. 8.5(0.0-17.5)] increased in schizophrenic patients (P<0.001). Among pro-inflammatory cytokines, the levels of IL-1α, IL-6, IL-11, IL-12A, IL-15, IL-17A and G-CSF in tears were elevated in schizophrenia group (all P<0.01). Most of the chemokines examined were increased in the tears of schizophrenics (all P<0.05). The levels of MMP-9 and ICAM-1 were also higher in schizophrenic patients (all P<0.001). The concentrations of IL-1Ra, TIMP-1 and TIMP-2 in schizophrenia group were decreased (all P<0.001). In schizophrenic patients, the level of CCL2 in tears was positively correlated with OSDI (R=0.34, P=0.03). The increasing TIMP-1 and decreasing IL-5 were correlated with increasing LLT (R=0.33, P=0.035; R=-0.35, P=0.027, respectively). Then, the level of ICAM-1 was positively correlated with PBR (R=0.33, P=0.035). There was a negative correlation between IL-8 and Schirmer I test (R=-0.41, P=0.009). Conclusions: Patients with schizophrenia were more likely to be accompanied by asymptomatic DED, with mild symptoms and obvious signs. The inflammatory cytokines in tears of schizophrenic patients differed greatly from that of non-schizophrenia.